Yesus Antara Zelot dan Eseni: Konstruksi Teologi Transformatif dalam Konteks Indonesia - Sheren Angela; Amos Sukamto; Tri Mulyanti (Sekolah Tinggi Teologi Berita Hidup, 2021)
Theological studies are often seen as normative and a religious teaching that is pure and unchangeable. This view causes theology to often become irrelevant to the context. Therefore, it is very important to increase efforts to construct transformative theology, especially in the Indonesian context, so that theology becomes relevant and able to become an answer to the problems of today's society. The presence of God in Jesus into the world is still mostly portrayed as the task of saving mankind from sin (John 3:16). The social ministry side of Jesus in the effort to transform society has not received enough attention. This article will analyze the path of social transformation that Jesus took by comparing the attitudes of the Zealots and the Essenes in responding to the problems that arise in society. The Zealots in responding to the realities of socio-political problems that occur around them tend to use violence (violence), whereas the Essenes tend to withdraw from the world (ascetic). Jesus is neither like the Zealots nor like the Essenes. Jesus entered into society (Non Ascetic), not using violence (Non Revolution), but through transformation (but through transformation). The method used is Hermeneutics by emphasizing historical, sociological and textual analysis to dissect some parts of Luke's Gospel. Through this article, it is hoped that it can provide alternatives to the construction of transformative theology in the Indonesian context, by imitating the praxis of the ministry of the Lord Jesus.Kajian teologi kerap kali dilihat sebagai suatu hal yang normatif dan merupakan suatu ajaran agama yang bersifat murni dan tidak dapat diubah. Pandangan tersebut mengakibatkan teologi sering menjadi tidak relevan lagi dengan konteks. Oleh karena itu sangat penting untuk memperbanyak usaha konstruksi teologi transformatif khususnya dalam konteks Indonesia, sehingga teologi menjadi relevan dan mampu menjadi jawaban bagi persoalan masyarakat masa kini. Kehadiran Allah dalam diri Yesus ke dalam dunia kebanyakan masih dipotret sebatas tugas penyelamatan manusia dari dosa (Yoh. 3:16). Sisi pelayanan sosial Yesus dalam usaha mentransformasi masyarakat masih belum mendapat perhatian yang cukup. Artikel ini akan menganalisis jalan transformasi sosial yang ditempuh Yesus dengan membandingkan sikap golongan Zelot dan golongan Eseni dalam merespons persoalan-persoalan yang muncul di dalam masyarakat. Golongan Zelot dalam merespons terhadap kenyataan-kenyataan persoalan sosial politik yang terjadi di sekitarnya cenderung dengan cara menggunakan kekerasan (violence), sebaliknya golongan Eseni cenderung menarik diri dari dunia (asketis). Yesus tidak seperti Zelot dan juga tidak seperti Eseni. Yesus masuk ke dalam masyarakat (Non Ascetic), tidak menggunakan kekerasan (Non Revolution), tetapi dengan jalan transformasi (but through transformation). Metode yang digunakan adalah Hermeneutika dengan memberi tekanan pada analisis historis, sosiologis dan analisis teks untuk membedah beberapa bagian Injil Lukas. Melalui artikel ini diharapkan dapat memberikan alternatif-alternatif konstruksi teologi transformatif dalam konteks Indonesia, dengan meneladani praxis pelayanan Tuhan Yesus.